Contribution by Unit Zakat, Sadaqah and Waqf to the UiTM’s students at Puncak Alam Campus / Ahmad Hafizul Hakim Sapiai - Sapiai, Ahmad Hafizul Hakim (Academy of Contemporary Islamic Studies (ACIS), 2016)
As explained in the Qur'an in general on prayer as well as in respect of zakat, Al-Qur'an does not explain in detail about the rate, nisab, the type of property that is subject to zakat and conditions of zakat but it can be clearly understood by the Hadith of the Prophet S.A.W. However, the Quran states clearly that zakat should be distributed to the eight specific recipients. Asnaf poor and needy urgently need fund in education because it is one of the most important aid to them because as important ticket that could change their lives and remove these people from poverty. So the zakat institutions must actively play a role in distributing zakat funds in the form of education to the recipients in Puncak Alam. Therefore, this research is aimed to identify the roles and contributions of zakat institution in helping the needy students. Some groups of students in UiTM Puncak Alam who have financial problems to continue their studies at universities can apply the zakat education to meet and fulfill their needs. This research also focused to review the effectiveness of zakat institution to university students with financial difficulties can complete their studies at UiTM Puncak Alam.